Shariah Accounting in Indonesia: Lessons and Inspirations From Pakistan - Ilham Akbar, Bastaka; Mukhlisin, Murniati (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This paper delves into the historical evolution of sharia accounting in Pakistan, reflecting on its significance and addressing contemporary challenges. This study discusses its relevance and future issues herein. Though this study focuses on a specific context of adopting Shariah into the overall framework of financial and economic sectors of Pakistan, the method incorporates the elements of historical methods, regulatory histories, industry evolutions. It analyses the significance of the sharia accounting on managerial practices, investment decisions and socio-economic growth. In this sense, the research exposes present-day problems and possibilities that apply to the continuous debate on Sharia accounting. Consequently, it provides a wealth of insight for Indonesia on the way forward to advancing Sharia accounting standards. The study uses Qualitative content analysis, according to the aim of ensuring that the research is holistic, a wide range of texts is used by the study.